1995
DOI: 10.1177/154193129503901814
|View full text |Cite
|
Sign up to set email alerts
|

Computer Modeling of a Nuclear Power Plant Operating Crew to Aid in Analysis of Crew Size Issues

Abstract: An analytical approach to addressing the implications of nuclear power plant shift sizing is needed as an augmentation to the classical empirical approach. The research reported in this paper was to evaluate the feasibility and validity of one potential analytical approach as a means of evaluating the consequences of crew reduction on crew performance in a nuclear power plant setting. The approach selected for analysis was task network modeling and simulation using a tool named Micro Saint. Task network modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In terms of a team, studies have found that teamwork assistance systems provide efficient communication strategies, reduce human error, support higher team performance and situational awareness, and organize the operator's crew (Furuta, Shimada, & Kondo, 1999;Hallbert, Sebok, Morisseau, & Persensky, 1997;Huang & Hwang, 2009;Plott, Scott-Nash, Hallbert, & Sebok, 1995;Skitka, 1999;Volpe, Cannon-Bowers, Salas, & Spector, 1996).…”
Section: Teamwork In the Mcr Of Anppsmentioning
confidence: 99%
“…In terms of a team, studies have found that teamwork assistance systems provide efficient communication strategies, reduce human error, support higher team performance and situational awareness, and organize the operator's crew (Furuta, Shimada, & Kondo, 1999;Hallbert, Sebok, Morisseau, & Persensky, 1997;Huang & Hwang, 2009;Plott, Scott-Nash, Hallbert, & Sebok, 1995;Skitka, 1999;Volpe, Cannon-Bowers, Salas, & Spector, 1996).…”
Section: Teamwork In the Mcr Of Anppsmentioning
confidence: 99%